EMR-based clinical decision support to address rising Clostridioides difficile rates in a pediatric hematology/oncology/BMT unit. Issue 28 (1st October 2022) - Stokes, Claire; Cotter, Jillian; Cost, Carrye Rudolph; Dorris, Kathleen McCarthy O'Toole; Lugo, Virginia; Child, Jason; Coughlin, Rebecca; Cox, Stephanie; Hazleton, Keith; Dominguez, Samuel
Abstract : 383 Background: The transition from conventional microbe detection methods to multiplex polymerase chain reaction-based gastrointestinal pathogen panels (GIP) has contributed to increased detection of Clostridioides difficile. Children undergoing cancer therapy often experience changes in stool patterns that present similarly to infectious diarrhea and they have high rates of C. difficile colonization, potentially leading to excessive testing and attendant false positive detection of C. difficile. In response to rising rates of C. difficile detection in our pediatric inpatient hematology/oncology/BMT unit, we developed and implemented a decision support tool to address rising rates of C. difficile for our population. Methods: A multidisciplinary team was convened in 2018 to develop an evidence-based clinical pathway for stool testing and C. difficile. treatment. A clinical decision support tool was designed and integrated into the electronic medical record (EMR) to guide providers in whether to order C.difficile testing in the presence or absence of broader GIP. This tool incorporated stool quality as documented by the Bristol stool scale and stool frequency, recent laxative administration, age, length of stay, and recent stool testing in order to limit C. difficile testing to those patients with high likelihood of infection. In parallel, a team focused on implementation of appropriate hand hygiene, universal gloving, ultraviolet disinfection, and signage to reduce colonization among our patients. Monthly rates of hospital acquired C. difficile. infections were followed from February 2018 through June 2020. Results: After introduction of the pathway and implementation of the stool testing restrictions, the rate of hospital-acquired C. difficile infection rate decreased from 27.6 to 14.3 infections per 10, 000 hospital days a, 48.1% reduction. Conclusions: After implementation of an EMR-based clinical decision support reinforcing evidence-based practice guidelines, we observed a meaningful reduction in C. difficile infections on a pediatric hematology/oncology/BMT unit. Continuous efforts towards environmental changes to reduce colonization in our population potentially contributed to our success.